The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00213-014-3758-0
|View full text |Cite
|
Sign up to set email alerts
|

Developmental exposure to SSRIs, in addition to maternal stress, has long-term sex-dependent effects on hippocampal plasticity

Abstract: There are long-term effects of developmental SSRI exposure on hippocampal plasticity that is differentially affected by expose to maternal adversity and offspring sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
57
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 102 publications
11
57
1
Order By: Relevance
“…Maternal postpartum fluoxetine increased density of doublecortin-expressing cells in the dorsal dentate gyrus in adult male offspring. This is at least partially consistent with a prior study which showed that maternal postpartum fluoxetine slightly increased density of doublecortin-expressing cells in adult male offspring and decreased it in the adult female offspring (Rayen et al, 2015). However, our results suggest that after behavioral testing, maternal postpartum fluoxetine stimulates doublecortin expression in the dorsal (but not ventral) dentate gyrus, and only in the adult male offspring.…”
Section: Maternal Postpartum Fluoxetine Increased Serotonin-mediated supporting
confidence: 87%
See 2 more Smart Citations
“…Maternal postpartum fluoxetine increased density of doublecortin-expressing cells in the dorsal dentate gyrus in adult male offspring. This is at least partially consistent with a prior study which showed that maternal postpartum fluoxetine slightly increased density of doublecortin-expressing cells in adult male offspring and decreased it in the adult female offspring (Rayen et al, 2015). However, our results suggest that after behavioral testing, maternal postpartum fluoxetine stimulates doublecortin expression in the dorsal (but not ventral) dentate gyrus, and only in the adult male offspring.…”
Section: Maternal Postpartum Fluoxetine Increased Serotonin-mediated supporting
confidence: 87%
“…This study used a higher dose of fluoxetine (10 mg/kg) than Rayen et al, 2015 (5 mg/kg). Regardless, maternal fluoxetine appears to increase doublecortin expression in adult males although this may be mitigated by prenatal stress (Rayen et al, 2015), but not by maternal postpartum CORT. Indeed, the increase in immature neurons due to maternal fluoxetine was only evident in the male offspring of CORT-treated dams.…”
Section: Maternal Postpartum Fluoxetine Increased Serotonin-mediated mentioning
confidence: 75%
See 1 more Smart Citation
“…Treating dams with FLX in the postpartum reversed the suppressive effect of prenatal stress on hippocampal DCX-expressing cells in both adolescent male and female offspring [17]. However, this interaction between prenatal stress and postpartum FLX exposure did not persist to adulthood as maternal postpartum FLX decreased number of DCX-expressing cells in offspring also exposed to prenatal stress, particularly in the males [29]. We recently reported that FLX given to the dam during the postpartum period increased density of DCX-expressing cells in the dorsal hippocampus of adult male offspring but not in adult female offspring [12].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found that depression reduces neuronal plasticity and impairs synaptic function, which may be an important target of pharmacological intervention (39). The anti-psychotic drug Lurasidone has shown to be effective in a CMS model through the modulation of synaptic and neuroplastic proteins and PSD-95 (40).…”
Section: Discussionmentioning
confidence: 99%